A Comparison of Perspectives of Inmates vs. Staff in Determining Critical Content for Occupational Therapy Transitional Programming with Female Inmates - Milliken, Barbara E. (Women & criminal justice, 2024)
The U.S. justice system focuses more on corrections than on rehabilitation. In countries emphasizing rehabilitation, occupational therapists are commonly employed. A comparative analysis was conducted of staff vs. inmates’ views of essential programming at one Midwestern U.S. women’s reintegration center. Inmates participated in two 90-min focus groups (N = 9) which included a 50-item quantitative survey. Staff (N = 16) were surveyed via an online platform. Qualitative and quantitative results showed that staff and inmates had limited knowledge of offerings. Both groups identified similar priorities, desiring whole health, professionally-led trauma-informed programming to support independent living, thus indicating a current role for occupational therapy.